2014
DOI: 10.1002/pc.23043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and creep behavior of poly(trimethylene terephthalate)/mesoporous silica composites

Abstract: The poly(trimethylene terephthalate) (PTT) containing mesoporous silica (SBA‐15) prepared by in situ polymerization were used as the master batch in this work and mixed with the commercial PTT to fabricate PTT/mesoporous silica composites. The mechanical properties and viscoelastic behaviors such as creep and creep recovery of as‐obtained composite system were then studied in detail. The results reveal an evident reinforcing effect of the mesoporous SBA‐15 particles at the lower loading levels. Compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Also, Liu et al . reported that the tensile strength and impact strength of the poly(trimethylene terephthalate) composite with 0.5 wt % of mesoporous silica (SBA‐15) particles increased by about 26% and 10%, respectively, which is attributed to the physical crosslinking between SBA‐15 and poly(trimethylene terephthalate) chain …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Liu et al . reported that the tensile strength and impact strength of the poly(trimethylene terephthalate) composite with 0.5 wt % of mesoporous silica (SBA‐15) particles increased by about 26% and 10%, respectively, which is attributed to the physical crosslinking between SBA‐15 and poly(trimethylene terephthalate) chain …”
Section: Resultsmentioning
confidence: 99%
“…Mesoporous material has been known as a very important basic material in many applicable research areas. It has been proved as an indispensable material in chemical, biological, electric, engineering, and fuel cell industry . Accordingly, nanocomposites prepared with polymer and mesoporous materials have been developed to find novel properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation